Research on User Satisfaction with Library Services at the Kaunas University of Technology - Tautkevičienė, Gintarė; Adomaitytė, Gerda (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English]
Keywords: user satisfaction; organizational performance; academic library; library services